Lateral cervical thymic cyst - Patıroğlu, Tahir E.; Soysaraç, Mehmet (The Turkish Journal of Pediatrics, 1983)
The case of a 6-year-old boy with a cervical thymic cyst on the right side of the neck is presented and the relevant literature is reviewed. Cervical thymic cysts, being in most cases situated laterally on the neck, have often been confused with cystic masses in the neck. Seventy-five percent of the patients were less than 20 years old. Eighty percent complained of a painless mass. The histological diagnosis was made if thymic epithelial elements and Hassall’s corpuscles could be found within and just adjacent to the cyst wall. Our case is the 74th case of cervical thymic cyst in the literature.